THE HAGUE CONVENTION ON THE INTERNATIONAL PROTECTION OF ADULTS: OVERVIEW AND CONVERGENCE WITH THE BRAZILIAN LAWCONVENÇÃO DA HAIA SOBRE A PROTEÇÃO INTERNACIONAL DE ADULTOS: PANORAMA E REFLEXOS SOBRE O ORDENAMENTO BRASILEIRO - Rodrigues, Diogo Luiz Cordeiro; Costa, Igor Pires Gomes da (Caderno de Relações Internacionais, 2020)
This article aims to give an overview of the Hague Convention on the International Protection of Adults, focusing on its scope as well as its rules of jurisdiction and those relating to applicable law. Moreover, based on the Brazilian case, this work discusses to what extent some underlying reasons for the Convention may indicate a degree of convergence between national and international rules regarding vulnerable adults.